2015
DOI: 10.1039/c5ra13569a
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin affords protection against valproic acid induced teratogenicity by curtailing oxidative stress and inhibiting CYP2C9 activity

Abstract: Administration of drugs during pregnancy is always done with immense caution, however multiple neurological ailments including epilepsy and depression warrant medical treatments even during pregnancy. This exposes the unborn fetus to killer teratogenic effects, thus warranting intense studies towards finding potential anti-teratogenic agents. We employed a valproic acid (VPA) induced model of fetotoxicity and teratogenicity in rats towards assessing the antiteratogenic activity of curcumin, an antioxidant well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Moreover, they have shown that curcumin could significantly decrease mentioned fetal anomalies as well as a causing a significant increase in live births, body weight, crown to rump length in valproic acid-treated pregnant animals. The mentioned protective effects are believed to be achieved through decreasing CYP2C9 expression, ROS, and thiobarbituric acid reactive substances (TBARS) as well as a significant increase in superoxide dismutase (SOD), reduced glutathione (GSH), and CAT [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, they have shown that curcumin could significantly decrease mentioned fetal anomalies as well as a causing a significant increase in live births, body weight, crown to rump length in valproic acid-treated pregnant animals. The mentioned protective effects are believed to be achieved through decreasing CYP2C9 expression, ROS, and thiobarbituric acid reactive substances (TBARS) as well as a significant increase in superoxide dismutase (SOD), reduced glutathione (GSH), and CAT [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…valproic acid etc) produces toxic ROS by impairing glutathione homeostasis and induced birth defects. 5,7 During gestation maternal circulation is directly linked to fetal circulation and the liver is the main site of drug metabolism hence, oxidative stress in the maternal system may induce oxidative stress in the foetuses which may cause fetotoxicity or embryotoxicity expressed in various ways including birth defects. 8 Some investigators also suggest that, increased oxidative stress to the developing foetus imposed by the intermediate metabolites of drugs (AEDs) may be responsible for the teratogenic effects.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 It has been reported by several workers, being an effective antioxidant, curcumin counteracts oxidative stress-induced damages by retrieving the situation of redox disequilibration and thus recovering the activity of endogenous antioxidative defense system. [5][6][7] Since more than 50% of pregnancies are unplanned, sometimes the situation becomes crucial when a woman comes to know that she has to undergo treatment with some medication like epileptic drugs (might be a teratogenic) while she is pregnant and she is neither allowed undergoing for 'Medical Termination of Pregnancy (MTP) nor keep the treatment pending until delivery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, curcumin affords dose dependent amelioration of the anomalies in fetus exerted by VPA. 56 A number of plant products have been reported to have excellent source of antioxidant with no side effects, in most of the published articles. Folic acid, vitamins and various plant products in various form now used as protective, prophylactic or ameliorative form.…”
Section: Anti-teratogenic Agents Against Vpa Induced Teratogenesismentioning
confidence: 99%